The Impact of Nutrition Education Programs on Healthy Eating Behavior Among Urban Adolescents - Djafir, Wa Ode Polan (Generasi Sains Indonesia, 2024)
This study examines the impact of a nutrition education program on improving nutrition literacy and promoting healthier eating behaviour among urban adolescents. The intervention aimed to enhance participants' knowledge of nutrition and encourage the adoption of healthier dietary habits. A quantitative research design was employed, with an experimental group receiving nutrition education and a control group not participating in the program. Pre- and post-tests were used to measure changes in nutrition literacy and eating behaviour. Statistical analyses, including paired sample t-tests, regression analysis, and ANOVA, were conducted to assess the effectiveness of the intervention. The results indicated that adolescents in the experimental group showed significant improvements in both nutrition literacy and healthy eating behaviour, with a reduction in the consumption of unhealthy foods. Socio-economic status did not significantly influence the effectiveness of the program, suggesting that nutrition education can be effective across diverse socio-economic backgrounds. This study contributes to the growing body of literature on nutrition education and provides valuable insights for developing effective interventions to combat poor dietary habits among urban youth. The findings highlight the importance of nutrition education as a tool for promoting long-term health improvements in adolescent populations.